2009
DOI: 10.1007/s00213-009-1665-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes

Abstract: Low BDNF levels at the onset of psychosis suggest that it may contribute to the pathogenesis of schizophrenia and perhaps, could be a candidate biological marker for positive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
3
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 30 publications
(52 reference statements)
13
96
3
4
Order By: Relevance
“…Most of the studies (12/16) measuring serum BDNF documented lower concentrations of this neurothropin in patients with schizophrenia (Carlino et al, 2011;Chen et al, 2009;Grillo et al, 2007;Ikeda et al, 2008;Jindal et al, 2010;Jockers-Schrübl et al, 2004;Pirildar et al, 2004;Rizos et al, 2008;Tan et al, 2005a;Toyooka et al, 2002;Xiu et al, 2009;Zhang et al, 2008); however, in other studies, BDNF concentrations were either increased (Gama et al, 2007;Reis et al, 2008); or normal (Huang et al, 2006;Shimizu et al, 2003) (Table 1). Five out of the 16 researches investigated gender effects, demonstrating either significantly lower or higher serum BDNF levels in males suffering from schizophrenia (Gama et al, 2007).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Most of the studies (12/16) measuring serum BDNF documented lower concentrations of this neurothropin in patients with schizophrenia (Carlino et al, 2011;Chen et al, 2009;Grillo et al, 2007;Ikeda et al, 2008;Jindal et al, 2010;Jockers-Schrübl et al, 2004;Pirildar et al, 2004;Rizos et al, 2008;Tan et al, 2005a;Toyooka et al, 2002;Xiu et al, 2009;Zhang et al, 2008); however, in other studies, BDNF concentrations were either increased (Gama et al, 2007;Reis et al, 2008); or normal (Huang et al, 2006;Shimizu et al, 2003) (Table 1). Five out of the 16 researches investigated gender effects, demonstrating either significantly lower or higher serum BDNF levels in males suffering from schizophrenia (Gama et al, 2007).…”
Section: Resultsmentioning
confidence: 97%
“…Six studies reported no diagnostic subtypes of schizophrenia (Ikeda et al, 2008;Gama et al, 2007;Jockers-Schrübl et al, 2004;Pirildar et al, 2004;Reis et al, 2008;Rizos et al, 2008;Toyooka et al, 2002) while in seven studies it was assessed the differences in serum BDNF levels among diagnostic subtypes Grillo et al, 2007;Huang et al, 2006;Shimizu et al, 2003;Tan et al, 2005a;Xiu et al, 2009;Zhang et al, 2008). Different forms of schizophrenia had no association with BDNF serum levels in 5 papers (Grillo et al, 2007, Shimizu et al, 2003Tan et al, 2005a;Xiu et al, 2009;Zhang et al, 2008), while Chen et al (2009) showed significantly higher BDNF levels in paranoid (10.4 ± 4.3 ng/ml) compared to undifferentiated (8.0 ± 3.9 ng/ml) and other combined subtypes (7.5± 4.1 ng/ml). Huang et al (2006) showed that patients with catatonic schizophrenia had lower serum BDNF protein levels than patients with paranoid schizophrenia and residual schizophrenia.…”
Section: Clinical Features Of Patientsmentioning
confidence: 99%
See 3 more Smart Citations